Magnesium supplementation beneficially affects depression in adults with depressive disorder: a systematic review and meta-analysis of randomized clinical trials - Moabedi, Mahdi; Aliakbari, Mohammadreza; Erfanian, Shima; Milajerdi, Alireza (Frontiers in Psychiatry, 2023)
The findings from randomized clinical trials examining the effect of magnesium supplementation on depression are inconsistence. We decided to conduct a meta-analysis that summarizes all the evidence on the impact of magnesium supplementation on depression scores in adult individuals with depressive disorder.We conducted a systematic search in the online databases using all related keywords up to July 2023. We included all randomized clinical trials examining the effect of magnesium, in contrast with placebo, on depression scores.Results: Finally, seven clinical trials were included in this systematic review, building up a total sample size of 325 individuals, with ages from 20 to 60 years average. These RCTs resulted in eight effect sizes. Our findings from the meta-analysis showed a significant decline in depression scores by intervention with magnesium supplements [Standardized Mean Difference (SMD): -0.919, 95% CI: -1.443 to -0.396, P =0.001].Our review suggests that magnesium supplementation can have a beneficial effect on depression. Future high-quality RCTs with larger sample sizes must be run to interpret this effect of magnesium on depression in clinical settings.